2023
DOI: 10.1021/acs.inorgchem.3c01726
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Dimensional Halides with ns2 Electron (Sb3+) Activation to Generate Broad Photoluminescence

Abstract: Organic−inorganic metal halides (OIMHs) have various crystal structures and offer excellent semiconducting properties. Here, we report three novel OIMHs, (PPA) 6 InBr 9 (PPA = [C 6 H 5 (CH 2 ) 3 NH 3 ] + ), (PBA) 2 SbBr 5 , and (PBA) 2 SbI 6 (PBA = [C 6 H 5 (CH 2 ) 4 NH 3 ] + ), showing typical zero-dimensional (0D) structure, octahedra dimers, and corner-sharing one-dimensional chains and crystallized in the monoclinic system with P2 1 , P2 1 /c, and C2/c space groups, respectively. (PPA) 6 InBr 9 , (PBA) 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…Tauc diagram analysis showed that the band gap of undoped sample PA 6 InCl 9 was 4.91 eV, and the band gap of PA 4 NaInCl 8 was 4.86 eV. With the introduction of Sb 3+ , the value of the band gap decreases from 4.82 and 4.80 eV to 4.71 and 4.70 eV with increasing doping concentration, respectively (Figure S8), which was consistent with previous reports. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Tauc diagram analysis showed that the band gap of undoped sample PA 6 InCl 9 was 4.91 eV, and the band gap of PA 4 NaInCl 8 was 4.86 eV. With the introduction of Sb 3+ , the value of the band gap decreases from 4.82 and 4.80 eV to 4.71 and 4.70 eV with increasing doping concentration, respectively (Figure S8), which was consistent with previous reports. …”
Section: Resultssupporting
confidence: 91%
“…However, indium-based halide perovskites have poor absorption capacity. To address this issue, effective doping of ns 2 metal ions can enhance the luminescence performance, achieving broadband emission with large Stokes shift and high PLQY. Furthermore, Sb 3+ as a metal cation with 5s 2 lone pair electrons has better stereo activity and structural tunability of lone pair electrons than that with 6s 2 lone pair electrons and has been widely used as an effective dopant to improve the PL performance. , In 2020, our group introduced Sb 3+ ions in Cs 2 NaInCl 6 to achieve efficient blue luminescence, with PL QY as high as ∼70%. This enhancement is attributed to the fact that Sb 3+ doping breaks the inherent parity-forbidden transition and effectively regulates the density of the state (DOS) population …”
Section: Introductionmentioning
confidence: 99%
“…The In–Br bond lengths of 1 are in the range of 2.5818(9)–2.7048(9) Å, while those of 2 are in the range of 2.5937(5)–2.6734(5) Å. These In–Br bond distances are slightly shorter than those of the previous report. ,, The distances of In–N are 2.301(6) and 2.311(6) Å in 1 and 2.303(3) and 2.316(3) Å in 2 , which are slightly shorter than those of [In 2 (phen) 3 Cl 6 ]·CH 3 CN . It is notable that the density of 2 is slightly greater than that of 1 .…”
Section: Resultsmentioning
confidence: 55%
“…The broadband emission in these WLE perovskites has been commonly attributed to intrinsic self-trapped excitons (STEs), , distinguishing them from conventional extrinsic defect emission dependent on sample doping and quality. , STEs, quasi-particles composed of localized excitons with deformed lattices, have been proposed in various materials, including condensed rare gases, organic molecule crystals, oxides, chalcogenides, and metal halides. In low-dimensional perovskites, excitons are formed by the binding of electrons and holes by quantum and dielectric confinement effects. Meanwhile, both long- and short-range exciton–phonon coupling is enhanced due to the soft and polar lattice and reduced dimensionality, facilitating STE formation. , Despite considerable reports of broadband emission in low-dimensional perovskites, the exact electronic and structural nature of these STE species remains elusive, hindering the rational design of high-efficiency WLE materials. …”
Section: Introductionmentioning
confidence: 99%